In situ pH management for microbial culture in shake flasks and its application to increase plasmid yield - Sanil, Reenu; Maralingannavar, Vishwanathgouda; Gadgil, Mugdha (Journal of Industrial Microbiology & Biotechnology, 2014)
Shake flasks are widely used to culture microorganisms, but they do not allow for pH control without additional infrastructure. In the presence of a carbon source like glucose, culture pH typically decreases due to overflow metabolism and can limit the growth of microorganisms in shake flasks. In this study, we demonstrate the use of magnesium hydroxide-loaded pH managing hydrogels (m-pHmH) for in situ base release to counter the decrease in culture pH in shake flasks using Escherichia coli as a model organism, in both complex and mineral salts medium. Base release from m-pHmH is shown to increase with decreasing pH (22-fold increase in release rate from pH 8 to 5), thus providing feedback from culture pH. The addition of m-pHmH resulted in better pH maintenance and higher biomass yields of E. coli K12 in media containing glucose as a carbon source. The use of m-pHmH with additional buffer resulted in pH being maintained above 6.9 while pH decreases below 5 without m-pHmH. We demonstrate one application of such in situ pH management to increase the volumetric plasmid yield from E. coli in shake flask culture. In situ glucose release through a hydrogel to mimic fed-batch culture along with the addition of m-pHmH resulted in a 395 % increase in volumetric plasmid yield to 38 mu g/ml in shake flask culture.
Keywords: In situ pH control; Magnesium hydroxide; pH-responsive base release; Shake flask culture

Differential responses of CHO cells adapted to limitation of inorganic phosphate, glucose or glutamine - Maralingannavar, Vishwanathgouda; Parmar, Dharmeshkumar; Pant, Tejal; Gadgil, Chetan; Panchagnula, Venkateswarlu; Gadgil, Mugdha (255th National Meeting and Exposition of the American-Chemical-Society (ACS) - Nexus of Food, Energy, and Water, 2018)

In situ base release for pH maintenance can allow shake flasks to better mimic bioreactor performance for CHO cell culture - Maralingannavar, Vishwanathgouda; Shenoy, Bharath R.; Hazarika, Jahnabi; Unnikrishnan, Divya; Prabhu, Anuja; Maity, Sunit; Gadgil, Mugdha (Journal of Chemical Technology & Biotechnology, 2018)
BACKGROUNDShake flasks are widely used for evaluating mammalian cells in suspension. Lack of pH control can contribute to differences in culture performance between them and bioreactors. This study evaluates whether a previously reported in situ base releasing hydrogel (pHmH) to counter pH decrease can enable shake flask cultures to better mimic bioreactor cultures. RESULTSCompared with bioreactor culture, fed-batch cultures of a recombinant Chinese hamster ovary (CHO) cell-line in shake flasks without pHmH showed a decrease in pH to 6.6, accompanied by 40, 60 and 22% lower peak cell density, lactate accumulation, and immunoglobulin G (IgG) titer, respectively. Use of pHmH allowed shake flasks to maintain pH above 6.8 and reduced this difference to 20, 30, and 15%, respectively, thus enabling culture performance in shake flasks to better mimic the bioreactor. IgG glycosylation profiles were similar in identically fed cultures across all three platforms. Application of pHmH hydrogel during clone screening was evaluated by comparing correlation between titers for five recombinant CHO clones in bioreactors and shake flasks with and without pHmH; a higher correlation was found in shake flasks with pHmH than without. CONCLUSIONIn situ base release through hydrogel can allow identically fed fed-batch cultures in shake flasks to better mimic cell growth, lactate accumulation and IgG titers in bioreactors, without additional infrastructure. (c) 2018 Society of Chemical Industry.

Superfluous glutamine synthetase activity in Chinese Hamster Ovary cells selected under glutamine limitation is growth limiting in glutamine-replete conditions and can be inhibited by serine - Maralingannavar, Vishwanathgouda; Parmar, Dharmeshkumar; Panchagnula, Venkateswarlu; Gadgil, Mugdha (Biotechnology Progress, 2019)
Passaging and expansion of animal cells in lean maintenance medium could result in periods of limitation of some nutrients. Over time, such stresses could possibly result in selection of cells with metabolic changes and contribute to heterogeneity. Here, we investigate whether selection of Chinese Hamster Ovary (CHO) cells under glutamine limitation results in changes in growth under glutamine-replete conditions. In glutamine-limiting medium, compared to control cells passaged in glutamine-rich medium, the selected cells showed higher glutamine synthetase (GS) activity and attained a higher peak viable cell density (PVCD). Surprisingly, in glutamine-replete conditions, selected cells still showed a higher GS activity but a lower PVCD. We show that in glutamine-replete medium, PVCD of selected cells was restored on (a) inhibition of GS activity with methionine sulfoximine, (b) supplementation of aspartate-without affecting GS activity, and (c) supplementation of serine, which is reported to inhibit GS in vitro. Consistent with the reported effect of serine, inhibition of GS activity was observed upon serine supplementation along with reduced growth of cells under glutamine-limiting conditions. The latter observation is important for the design of glutamine-free culture medium and feed used for GS-CHO and GS-NS0. In summary, we show that CHO cells selected under glutamine limitation have superfluous GS activity in glutamine-replete medium, which negatively affects their PVCD. This may be due to its effect on availability of aspartate which was the limiting nutrient for the growth of selected cells in glutamine-replete conditions.
Keywords: C-13 tracer analysis; CHO cells; glutamine limitation; Glutamine synthetase; GS-CHO; GS-NS0; selection under nutrient limitation; serine